Dipeptidyl peptidase-3 is associated with severity of liver disease and circulatory complications in patients with cirrhosis. (17th February 2022) - Voiosu, Andrei Mihai; Wiese, Signe; Goetze, Jens Peter; Hartmann, Oliver; Voiosu, Theodor; Santos, Karine; Møller, Søren
Abstract: Background: Patients with cirrhosis suffer from a complex multiorgan disturbance and their prognosis is influenced by the development of portal hypertension and systemic circulatory dysfunction. Although non-invasive techniques such as transient elastography aid in early detection, there is an unmet need for reliable markers of these clinically significant complications. Methods: We conducted an exploratory single-center study investigating dipeptidyl peptidase-3 (DPP3) concentrations in various vascular beds in a cohort of 48 patients with cirrhosis and 16 healthy controls. Liver vein catheterisation with sampling from femoral artery and femoral, renal and hepatic veins as well as measurement of hepatic pressure and liver function via indocyanine green and galactose elimination tests were performed. Results: DPP3 concentrations were higher in cirrhotic patients compared to controls (12.6 vs. 7.4  ng/mL, p  = 0.006) and increased according to the severity of cirrhosis. DPP3 associated with MELD-Na score, Child class, indocyanine green clearance, increased DPP3 with the increased hepatic venous pressure gradient ( p  = 0.015) as well as increased heart rate and reduced systemic vascular resistance. DPP3 concentrations predicted the presence of clinically significant portal hypertension in cirrhotic patients (AUROC 0.78, 95% CI 0.65–0.9). Conclusion: DPP3 is a promising marker for portal hypertension and systemic hemodynamic changes in cirrhosis.